Encyclopedia of the Vietnam War (Scribner, 1996)
This authoritative encyclopedia separates the facts of America's longest war from the polemics that obscured them. It is an invaluable look at the people, places, events, and ideas - both on the battlefield and on the home front - of this confusing and contentious period. Readers will appreciate the even-handed treatment of the war that shaped and continues to shape America at the end of the twentieth century. Its 564 articles, 210 illustrations, and 13 maps provide the essential details about figures great and small - from Lyndon Johnson and Ho Chi Minh to the people in Vietnam's cities and countryside and the soldiers of all sides who fought and died in Southeast Asia. Ten long essays delve into major themes such as the war's effects on the United States and Vietnam, the land and peoples of Vietnam, and the French colonial era.